Identification of priority areas for restoration and conservation in two environmental protection area in the state of São Paulo: APA Piracicaba and Corumbataí (Research, Society and Development, 2022)
The habitat loss and the connectivity reduction in the landscape cause several environmental problems, such as extinctions and biodiversity decrease. Environmental restoration is one way to mitigate these effects and aims to recover areas of natural habitat, reconnecting isolated areas of natural vegetation. The amount of vegetation around the fragments may be an important factor to select areas when the restoration efficiency is sought. This work aims to analyze the landscape in the APA Corumbataí, APA Piracicaba, and in their municipalities, prioritizing areas to be restored and conserved. The analysis was based on the metrics of functional connectivity, according to the gap crossing capacity of species, and the habitat amount in the landscape. Landscapes with habitat amount between 20% and 60% are indicated for restoration, and above 60% for conservation. An important region of 47,987 hectare of cerrado and forest functionally connected in the study area was identified. Specifically, from Corumbataí to São Pedro, there is a zone with their last remnants of cerrado, making them an important area when the cerrado restoration of São Paulo state is craved. In addition, in Brotas, Analândia, Itirapina, and São Carlos there are areas with high percentages of native vegetation with potential for conservation, besides several others in the study area with habitat amount that have potential for restoration. Thus, the identification of areas with potential for restoration may be an important tool for territorial management.